SARS‐CoV‐2 vaccine acceptability among caregivers of childhood cancer survivors. Issue 6 (17th November 2021) - Wimberly, Courtney E.; Towry, Lisa; Davis, Elizabeth; Johnston, Emily E.; Walsh, Kyle M.
Abstract: Objective: To explore willingness/hesitancy to vaccinate self and children against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) among caregivers of childhood cancer survivors (CCS). Methods: A 19‐question survey was sent to caregivers of CCS and completed between February 25 and April 13, 2021. Logistic regression was used to investigate relationships between willingness/hesitancy to vaccinate (a) self and (b) CCS, and demographic variables, confidence in the government and medical community's responses to coronavirus disease 2019 (COVID‐19), and factors specific to the CCS community (e.g., previous participation in an investigational therapeutic trial). Results: Caregivers (6% male) from 130 unique families completed the survey. Mean CCS age at survey was 15 years (SD 6.4). Mean CCS age at diagnosis was 4.3 years (SD 4.3). Mean time from CCS diagnosis to survey completion was 10 years (SD 6.2). Twenty‐one percent of caregivers expressed hesitancy to vaccinate themselves and 29% expressed hesitancy to vaccinate their CCS. Caregivers expressing confidence in the federal government's response to COVID‐19 were six‐fold likelier to express willingness to self‐vaccinate ( p < .001) and were three‐fold likelier to express willingness to vaccinate their CCS ( p = .011). Qualitative analysis of free‐text responses revealed three general themes, including (a) confidence in science, medicine, and vaccination as a strategy for health promotion, (b) confidence in SARS‐CoV‐2 vaccination and belief that CCS are at greater risk of COVID‐19 complications, and (c) concerns about the swiftness of COVID‐19 vaccine development and insufficient safety/efficacy data in children and CCS. Conclusions: Results underscore the need for COVID‐19 vaccination education and outreach, even among families highly engaged with the medical community, and emphasize the importance of updating these families as relevant data emerge from vaccine trials and registries.